Performance and durability of a layered proton conducting solid oxide fuel cell fueled by the dry reforming of methane - Guo, Y.; Wan, T.; Zhu, A.; Shi, T.; Zhang, G.; Wang, C.; Yu, H.; Shao, Zongping (Royal Society of Chemistry, 2017)
© 2017 The Royal Society of Chemistry. Catalyst layers derived from La 2 NiO 4 , LaNiO 3 and Ni/La 2 O 3 precursors were applied to a conventional Ni-based anode in a proton conducting solid oxide fuel cell (H + -SOFC) for the dry reforming of methane with CO 2 . The phase structures, microstructures and catalytic activities of catalysts from the different precursors were systematically investigated. The cell performance and durability of a H + -SOFC with a catalyst layer (layered H + -SOFC) were examined. The layered H + -SOFC had higher cell performances than the conventional H + -SOFC. However, catalyst deactivation and degradation of the cell performance were observed as carbon deposition occurred on the catalyst layer due to CO disproportionation in exhaust gas at a high partial pressure of CO. The structure of carbon deposited on the catalysts was also investigated.